An Integrated Architecture for Lean Waste Analysis - Abdullah, Rohana; Abd Rahman, Md Nizam (2012)
Lean has become very popular for companies striving towards reducing wastes and improving their efficiency. The fundamental work in Lean implementation includes establishing the standard times for the process under study before the information can be used to determine the resource capacity. The traditional work study methods such as Process Mapping and Man-Machine Charts are no longer suitable to be used in the complicated manufacturing environment such as in the electronics. This paper reports on an integrated architecture for conducting work study and performing lean waste analysis. The developed architecture was implemented at an electronic manufacturing company. The benefits observed from the implementation phase indicate that the proposed architecture has reduced the lengthy time that work-study usually takes, eliminated human error during analysis and improved the accuracy of data.